2007
DOI: 10.1080/10715760601087558
|View full text |Cite
|
Sign up to set email alerts
|

The reactivity of carotenoid radicals with oxygen

Abstract: The possibility that carotenoid radicals react with oxygen to form chain-carrying peroxyl radicals has been postulated to account for the reduction in antioxidant effetiveness displayed by some carotenoids at high oxygen concentrations. The primary objective of the work described in this paper was to measure the rate constants for oxygen addition to a series of carotenoid radicals and to examine any influence of carotenoid structural features on these rate constants. Laser flash photolysis has been used to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…The nitrogen dioxide reaction with lycopene leads to only lycopene radical cation while the γ‐radiation produces reducing species (solvated electron, superoxide and hydrogen atoms) as well as hydroxyl radicals. The hydroxyl radical can add to many substrates and, with lycopene , this would produce the lycopene‐hydroxyl radical adduct (true˙Lyc‐OH) and hence, lycopene will protect the cells by removing the reactive hydroxyl radical. Our new results show this is a less efficient cell protection process in air than removal of oxidizing radicals via formation of the carotenoid radical cation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nitrogen dioxide reaction with lycopene leads to only lycopene radical cation while the γ‐radiation produces reducing species (solvated electron, superoxide and hydrogen atoms) as well as hydroxyl radicals. The hydroxyl radical can add to many substrates and, with lycopene , this would produce the lycopene‐hydroxyl radical adduct (true˙Lyc‐OH) and hence, lycopene will protect the cells by removing the reactive hydroxyl radical. Our new results show this is a less efficient cell protection process in air than removal of oxidizing radicals via formation of the carotenoid radical cation.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible product is the neutral lycopene radical formed via hydrogen atom abstraction . In the presence of oxygen, either radical may add molecular oxygen to form reactive peroxyl radicals leading to species such as true˙OOLycOH. We propose that, in our cellular system, such peroxyl radicals are formed in increasing concentration as the oxygen concentration increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5) leading to formation of the radical cation, adducts, ion-pairs and carotenoid neutral radicals 41. Previous work has shown that carotenoids can react with thyil radicals and acylperoxyl radicals by addition across the polyene chain to form neutral radicals (PhS-Car • and Acyl-Car-OO • ) that absorb in the visible region (450–550 nm) 42,43. It has also been reported that canthaxanthin and astaxanthin neutral radicals can be generated by first forming the radical anion (eq.…”
Section: Resultsmentioning
confidence: 99%
“…48 The rate constant for the addition of O 2 to a RAF radical is inversely proportional to the length of its conjugated system. 49 In less polar environments, CARs react with NO 2 • via HAT or RAF. Either way, the resulting radical intermediate should be relatively nonreactive toward O 2 addition (eq 2).…”
Section: → • Initiation: Rh Rmentioning
confidence: 99%